Safe Transitions for Every Patient - Paul Koch; Nancy Havas; Emily Densmore; Staci Young; Laura Currey; Karen Marcdante; Deborah Simpson (Association of American Medical Colleges, 2011)
Abstract Ineffective care transitions result in medical errors and compromised patient care. While improving trainees' ability to provide safe care transitions is a vital element in improving quality and safety of patient care, most of the current efforts available focus on the hospital perspective. Our goal was to develop a brief, 2-hour session that emphasizes effective communication of information between providers across care settings and disciplines for every patient. A PowerPoint presentation, with annotated speaker notes, provides definitions and describes the societal and personal impact of ineffective care transitions. Next, students are taught a care transitions communication mnemonic (PRIMARY) that is useful across providers/care settings. Finally, students participate in a faculty-facilitated small-group discussion featuring student-generated examples of care transitions and specific exercises applying the PRIMARY mnemonic to generate a dialogue between sender and receiver using incidents with a structured feedback worksheet. A seven-item quiz, along with learner and facilitator evaluation forms, completes the packet. Designed for medical students, the session is adaptable to any health professions discipline. Learners and facilitators rated the session highly, stating that objectives were achieved and that overall time, balance of small-group and large-group exercises, and use of the mnemonic were all valuable. The significance of this workshop is its emphasis on patient care and safety as students experience increasing levels of involvement in the communication of information for a patient care transition.